Colour Matching for Imaging Retrieval - MEHTRE, Babu M. (Institutional Knowledge at Singapore Management University, 1995)
Color is an important attribute for image matching and retrieval. We present two new color matching methods, the Reference Color Table Method and a Distance Method, for image retrieval. Both these methods and an existing method Histogram Intersection were implemented and tested for a database size of 170 color images. To compare the efficacy of each method, a figure of merit, called Efficiency of Retrieval, is defined. The results show that both the new methods perform better than the existing method, and that the Reference Color Table Method gives the best results.